Respuesta :
When you multiply two binomials, you should FOIL (first, outer, inner, last).
First:
2x*2x=4x^2
Outer:
2x*-3=-6x
Inner:
3*2x=6x
Last:
3*-3=-9
Pur it all together:
4x^2-6x+6x-9
Simplify:
4x^2-9
Final answer: 4x^2-9
First:
2x*2x=4x^2
Outer:
2x*-3=-6x
Inner:
3*2x=6x
Last:
3*-3=-9
Pur it all together:
4x^2-6x+6x-9
Simplify:
4x^2-9
Final answer: 4x^2-9
This one is not correct. You used the distributive property wrong. Using the FOIL method, 2x times -3 is -6x, while 2x times 3 is 6x. Since one is 6x and one is -6x, these terms cancel out. Therefore, the correct answer should be 4x^2 - 9.
You could also get this from doing (a+b)(a-b) = a^2 - b^2, but I wouldn't worry about that now.
You could also get this from doing (a+b)(a-b) = a^2 - b^2, but I wouldn't worry about that now.